INDEFINITE, PARTITIVE STRUCTURES AND THEIR INDIVIDUALISED “READING” - Laura IONICA (Studii si Cercetari Filologice: Seria Limbi Straine Aplicate, 2010)
The distinction mass - count nouns has always been long discussed by grammarians due to their difficulty in finding a homogenous point of view. The present study aims to clarify the different interpretations of massive nouns, laying stress on their individualized “reading”. Starting from different occurrences of massive nouns there has been established the role played by the indefinite article a/ an in structures comprising a massive entity.